2020
DOI: 10.3389/fbioe.2020.603514
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 8-Azaguanine Biosynthesis–Related Genes Provides Insight Into the Enzymatic and Non-enzymatic Biosynthetic Pathway for 1,2,3-Triazole

Abstract: 8-Azaguanine (1) is a special 1,2,3-triazole containing natural product that possesses potent antibacterial and antitumor activities. In the present study, the entire 8-azaguanine biosynthetic gene cluster was located from Streptomyces CGMCC4.1633. Targeted gene disruption, heterologous expression analysis, and feeding experiments identified crucial genes for 8-azaguanine production. Moreover, we characterized the structure of two novel metabolites, analyzed NO (or reactive nitrogen species) related genes 8-az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Rapid expansion of genomic information has revealed the abundant, yet unexploited biosynthetic potentials of natural products with intriguing biological activities arising from unique functional groups, such as those containing nitrogen–nitrogen (N–N) covalent bonds. N–N bond-forming reactions are integrated within the biosynthetic pathways of various classes of natural products, including polyketides, nonribosomal peptides, amino acid-, sugar-, and nucleoside-derivatives, and others. Recent studies have revealed various enzymatic machineries for the biogenesis of N–N bond-containing functional groups, such as the nitrite-utilizing ATP-dependent enzyme CreM and its homologues, several distinct groups of metalloenzymes, and the nitrite-utilizing transmembrane protein AzpL …”
Section: Introductionmentioning
confidence: 99%
“…Rapid expansion of genomic information has revealed the abundant, yet unexploited biosynthetic potentials of natural products with intriguing biological activities arising from unique functional groups, such as those containing nitrogen–nitrogen (N–N) covalent bonds. N–N bond-forming reactions are integrated within the biosynthetic pathways of various classes of natural products, including polyketides, nonribosomal peptides, amino acid-, sugar-, and nucleoside-derivatives, and others. Recent studies have revealed various enzymatic machineries for the biogenesis of N–N bond-containing functional groups, such as the nitrite-utilizing ATP-dependent enzyme CreM and its homologues, several distinct groups of metalloenzymes, and the nitrite-utilizing transmembrane protein AzpL …”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a significant increase in our knowledge of the biogenesis of NÀ N heterocycles, including those of piperazic acid, [25] 1,2,3-triazole, [26,27] 1,2,3-triazine, [28] 1,2,4-triazine, [29] and pyridazine. [30,31] Among them, piperazic acid was the sole example of an NÀ N heterocycle that is proved to be generated in an enzyme-dependent manner.…”
Section: Methodsmentioning
confidence: 99%
“…pathocidicus (Anzai et al 1961 ). Recently, a biosynthetic gene cluster responsible for the synthesis of 8AG in Streptomyces was located, and a complete biosynthetic pathway of 8AG was proposed (Zhao et al 2020 ; Hou et al 2020 ). Intrinsic fluorescence properties of 8AG can be utilized for monitoring the reaction of ribosylation/phosphorolysis catalyzed by the purine nucleoside phosphorolysis (PNP) enzyme (Wierzchowski et al 2004 , 2005 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%